Understanding Language Testing Impacts in Optimizing Its Positive Washback - Refanja Rahmatillah; Rizki Fajrita; Endah Anisa Rahma; Veni Nella Syahputri (Universitas Teuku Umar, 2021)
This article aims to discuss the impacts of language testing on someone’s personal life continuance and how language teachers should compromise to this reality and bring out the positive impacts that language testing can have on language learning (positive washback). The rationale of position of language testing in determining the flow of education, job and movement is firstly reviewed and then the cases of language testing impacts on various contexts is explored from previous studies. We then try to point out the main keys to maintain and optimize the positive washback from the existence of language testing. The consideration includes a good coordination between test producers, teachers and test-takers. Teachers, in addition, should provide follow-up teaching activities from the results of the students’ tests.